Blocplan Algorithm for Facility Layout Design in Various Industry in Indonesia - Iing Pamungkas; Abdiel Khaleil Akmal; Heri Tri Irawan (Jurnal Inotera, 2024)
Facility layout is an important aspect in planning and developing production facilities. A good layout can increase efficiency, productivity and safety in the production process. The Blocplan algorithm is a layout design method that can produce an efficient layout. This method uses a heuristic algorithm to find layouts based on having the highest R-Score value. The Blocplan algorithm has been applied in various industries in Indonesia because of its advantages which can produce a more efficient layout compared to the initial layout. Based on this, it is necessary to study the use of the Blocplan algorithm in designing facility layouts in various industries in Indonesia. This review aims to determine the use of the Blocplan algorithm in designing facility layouts in various industries in Indonesia. The review results show that layout design using the Blocplan algorithm can produce a layout that is more efficient than the initial layout. It was found that several related industries in Indonesia can use the Blocplan algorithm in redesigning facility layouts, including the pharmaceutical industry, construction project implementation, food industry, steel or iron industry, spring bed production, PVC production, transformer production, valve production, production trolleys, corn milling, feed processing, plastic recycling, garment or convection industry, robotization industry, coffee production, paper production, brick production, and wood processing.